Handling practices and microbiological assessment of wooden and plastic cutting boards in domestic kitchens - de Oliveira, Janaina Prieto [UNESP]; da Silva, Dionice Capistrano [UNESP]; Tadielo, Leonardo Ereno; dos Santos, Emanoelli Aparecida Rodrigues [UNESP]; da Silva, Evelyn Cristine [UNESP]; Sampaio, Aryele Nunes da Cruz Encide [UNESP]; Possebon, Fábio Sossai [UNESP]; Pereira, Juliano Gonçalves [UNESP] (Elsevier, 2025)
This study assessed the handling practices and microbiological characteristics of wooden and plastic cutting boards in households in a Brazilian city. A total of 100 boards were collected, along with a survey on their use. Bacteria were extracted from circular fragments (4.4 cm diameter) through sonication and analyzed for aerobic mesophilic bacteria, Enterobacteriaceae, Pseudomonas spp., Listeria monocytogenes, and Escherichia coli. Bacterial counts were expressed in log CFU/cm2, and pathogen presence was recorded. A 2.2 cm fragment was also examined via scanning electron microscopy. Survey results showed that 87% of food handlers used the same board for all foods, and 75% had used their board for over two years. Plastic boards had higher counts of aerobic mesophilic bacteria and Enterobacteriaceae (p < 0.05). However, newer wooden boards also showed high bacterial counts (p < 0.05). L. monocytogenes was detected in 3% of samples, and E. coli in 5%, with no significant differences between materials. These findings highlight cutting boards as potential cross-contamination sources and emphasize the presence of L. monocytogenes. Proper handling practices are essential to reducing contamination risks, especially in households.
Keywords: Biofilms; Cutting boards; Foodborne disease; Listeria monocytogenes; Surface contamination